2017
DOI: 10.1002/hec.3591
|View full text |Cite
|
Sign up to set email alerts
|

State Medicaid fees and access to primary care physicians

Abstract: Medicaid and uninsured patients are disadvantaged in access to care and are disproportionately Black and Hispanic. Using a national audit of primary care physicians, we examine the relationship between state Medicaid fees for primary care services and access for Medicaid, Medicare, uninsured, and privately insured patients who differ by race/ethnicity and sex. We found that states with higher Medicaid fees had higher probabilities of appointment offers and shorter wait times for Medicaid patients, and lower pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 17 publications
0
26
0
Order By: Relevance
“…More generous reimbursement and coverage may account for increased appointment offers to Medicare and privately-insured patients with weight concerns since physicians are sensitive to reimbursements, particularly for non-urgent needs (Clemens and Gottlieb, 2014). The Medicaid program has historically suffered low reimbursement rates which has been found to limit access (Decker, 2012; Sharma et al, 2017). Prior research suggests that states with better Medicaid coverage of tobacco cessation have higher rates of smoking cessation (e.g., Greene et al, 2014), but sensitivity analyses on our data found that access to new patient appointments for patients with smoking concerns was no better in states with better Medicaid coverage of tobacco cessation services.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…More generous reimbursement and coverage may account for increased appointment offers to Medicare and privately-insured patients with weight concerns since physicians are sensitive to reimbursements, particularly for non-urgent needs (Clemens and Gottlieb, 2014). The Medicaid program has historically suffered low reimbursement rates which has been found to limit access (Decker, 2012; Sharma et al, 2017). Prior research suggests that states with better Medicaid coverage of tobacco cessation have higher rates of smoking cessation (e.g., Greene et al, 2014), but sensitivity analyses on our data found that access to new patient appointments for patients with smoking concerns was no better in states with better Medicaid coverage of tobacco cessation services.…”
Section: Discussionmentioning
confidence: 99%
“…Data are from an annual, nationwide audit (Sharma et al, 2015; Sharma et al, 2017; Tinkler et al, 2017). Since 2013, trained research assistants (RAs) have called primary care physicians’ offices on behalf of a purported aunt or uncle requesting information about the earliest available new patient appointment for a physical exam.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…3 More generally, several studies leveraging pre-fee bump data show that higher Medicaid reimbursement rates or capitation payments for primary care services increased access to primary care. For instance, boosts in the reimbursement rate increased provider acceptance of Medicaid patients (Decker 2012) and appointment availability for enrollees (Sharma, Tinkler et al 2018).…”
Section: Related Literaturementioning
confidence: 99%